2017
DOI: 10.1002/art.39973
|View full text |Cite|
|
Sign up to set email alerts
|

The Development of Psoriatic Arthritis in Patients With Psoriasis Is Preceded by a Period of Nonspecific Musculoskeletal Symptoms: A Prospective Cohort Study

Abstract: A preclinical phase exists in patients with PsA prior to the diagnosis of the disease. This phase is characterized by nonspecific musculoskeletal symptoms, including joint pain, fatigue, and stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 27 publications
7
103
0
4
Order By: Relevance
“…Preclinical phase of PsA can exist in psoriasis prior to the diagnosis of the disease, which is characterized by nonspecific musculoskeletal symptoms, including fatigue and stiffness [30], which may explain subclinical MSUS findings in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Preclinical phase of PsA can exist in psoriasis prior to the diagnosis of the disease, which is characterized by nonspecific musculoskeletal symptoms, including fatigue and stiffness [30], which may explain subclinical MSUS findings in our study.…”
Section: Discussionmentioning
confidence: 70%
“…The existence of a preclinical phase in patients with PsA prior to the diagnosis of the disease has recently been reported [36]. This phase is characterized by nonspecific musculoskeletal symptoms, including joint pain, fatigue, and stiffness preceding the development of PsA; a symptom constellation not unlike the one found in patients with FM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Eder et al . has found that in patients with psoriasis, PsA is preceded by a period of nonspecific symptoms including fatigue . High concentrations of proinflammatory cytokines, such as tumour necrosis factor alpha, play a role in the pathogenesis of psoriasis and PsA, and also in fatigue and depression .…”
Section: Severity Of Fatigue In Patients Attending For Phototherapy mentioning
confidence: 99%